State-owned banks and international shock transmission - Marcin Borsuk; Oskar Kowalewski; Pawel Pisany (European Central Bank (ECB), 2022)
In this study, we reassess the links between commercial bank ownership and lending growth during the 1996-2019 period. We find evidence that the lending activities of foreign state-controlled and foreign privately owned banks differ, particularly during different crisis type periods and origins. Foreign state-controlled banks' loan growth rates are higher than those of foreign privateowned banks during host banking crises. By contrast, foreign state-controlled banks reduce their credit growth during a home banking crisis, while foreign private-owned banks increase lending in the host countries. Moreover, we find evidence that bank-specific characteristics were more important determinants of credit growth than ownership structure during the global financial crisis of 2008 and gain in importance in the post-crisis period.
Keywords: G01; G21; G28; 330; foreign banks; state-controlled banks; credit growth; crisis; internal capital market